(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Antenatal test is done to evaluate fetus health and the risk of adverse outcomes during the course of a pregnancy. Amniotic fluid is an important part of pregnancy which plays a vital role in the normal growth of the fetus and, promotes muscular-skeletal development and allows for easier fetal movement. The aim of this study was to assess the perinatal outcomes in pregnant women having borderline amniotic fluid index. Methods this was a prospective case control that was conducted on all Pregnant women who were enrolled from patients attending Zagazig university hospitals and Al-Ahrar teaching hospital for antenatal care. patients are divided into two groups: 1- Group A: will include 42 patients with normal AFI (8-22cm). 2- Group B: will include 42 patients with borderline AFI (5-8 cm). Results This study revealed no statistically significant difference between two groups (patients and control) regarding Gestational age of the baby, age, induction of labour, fetal distress syndrome, delivery, liquor and APGAR score while there was highly statistically significant difference between two groups regarding Amniotic fluid index and the baby weight. Also, this study showed statistically significant between two groups regarding NICU. Regarding the correlations of AFI, there was non statistically significant difference found between Amniotic fluid index and Complications, Induction of labour, Fetal distress syndrome, Delivery, APGAR, BABY WT (kg) and NICU, and there was highly statistically significant difference found between Amniotic fluid index and Gestational age(Week), and there was highly statistically significant difference found between Amniotic fluid index and LIQUOR, and there was statistically significant difference found between Amniotic fluid index and Fetal distress syndrome. Most of the cases and controls were belonging to age group 18-33 years i.e. cases 52% and controls 51%. The mean age of cases was 24.12±3.01 years in cases and 25.10 ± 3.78 years for controls. Sixty nine women were induced and 15 were failed induction in the cases, while only 1 woman was induced in the controls. The decision for induction or allowing for spontaneous labor was taken depending upon the stage of labor, favorability of the cervix and AFI. In our study, there was no statistically significant difference found between two groups regarding APGAR. There was no statistically significant difference found between two groups regarding liquor. Conclusion Adverse perinatal outcome is seen in higher percentage of patients having oligohydramnios than that of borderline AFI.